Olive Leaf Extract from Sicilian Cultivar Reduced Lipid Accumulation by Inducing Thermogenic Pathway during Adipogenesis - Palmeri, Rosa; Monteleone, Julieta I.; Spagna, Giovanni; Restuccia, Cristina; Raffaele, Marco; Vanella, Luca; Li Volti, Giovanni; Barbagallo, Ignazio (Frontiers in Pharmacology, 2016)
Olive leaves contain a wide variety of phenolic compounds belonging to phenolic acids, phenolic alcohols, flavonoids and secoiridoids, and include also many other pharmacological active compounds. They could play an important role in human diet and health because of their ability to lower blood pressure, increase coronary arteries blood flow and decrease the risk of cardiovascular diseases. The aim of this study was to investigate the effect of Olive leaf extract (OLE) from Sicilian cultivar on adipogenic differentiation of human adipose derived mesenchymal stem cells and its impact on lipid metabolism. We showed that OLE treatment during adipogenic differentiation reduces inflammation, lipid accumulation and induces thermogenesis by activation of uncoupling protein UCP1, SIRT-1, PPARα and Pgc-1α. Furthermore, OLE significantly decreases the expression of molecules involved in adipogenesis and upregulates the expression of mediators involved in thermogenesis and lipid metabolism. Taken together, our results suggest that OLE may promote the brown remodeling of white adipose tissue inducing thermogenesis and improving metabolic homeostasis.